Sistem Informasi Penjualan Pemasangan Kacafilm “HS Auto Film" - Noer Tjahja Moekthi Pratjitana; Kodrat Iman Satoto; Rinta Kridalukmana (Jurnal Teknologi dan Sistem Komputer, 2013)
The growing market share in many business areas especially in service area is causing the use of conventional accounting system being ineffective. One of the companies which still using the conventional one is a window film set-up service company called HS Auto Film. The process of processing sales data is less accurate and slower in the contrary of the developing sales data.  Computer-based window film set-up Sales Information System is built in order to make the processing data more accurate and faster. The information system is built using Visual Basic programming language along with .NET framework technology and SQL Server database that embedded in the application itself. The making and development process of the Sales Information System is using waterfall method.  Waterfall method consists of user requirement, analysis, design, implementation, and testing. Entity Relationship Diagram, Data Flow Diagram and Flowchart are also used in the Information System design.The output of this application design is a desktop application that can help user to control the set-up of window film, manage payment bill, and manage document in accounting in faster and more accurate way. The information system can be developed later using web-based system so that the development and maintenance can be done easier.